Pengaruh Budaya Kerja, Kepemimpinan, dan Keterlibatan Karyawan terhadap Kinerja Karyawan melalui Perencanaan Karier - ABID IBNU HUSEN; Lili Karmela Fitriani; Odang Supriatna (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
buAbstract. This research was conducted to find out and provide advice in the form of program recommendations and company policies related to the influence of work culture, leadership, and employee involvement on employee performance through career planning at the Puspita Cipta Group (PCG) Oil and Gas Unit in Kuningan Regency. The method used is quantitative with a questionnaire distribution technique. The population taken was 230 people with details: 80 Head Office employees, 60 from SPPBE, 54 from Gas Stations (SPBU), and 36 from BPT. Based on proportional calculations from Taro Yamane's theory (Riduwan, 2015: 65) by determining the number of samples using the formula n = N / NdÂ² + 1, so that a sample of 146 respondents emerged with details: 51 from the Central Office, 38 from SPPBE, 32 from Gas Stations (SPBU), and 25 employees from BPT. The questionnaire distribution data collected was then processed by testing validity, reliability testing, and hypothesis testing. This research resulted in a discussion that work culture and employee involvement have a positive and significant effect on career planning and employee performance, leadership has no effect on career planning and employee performance, career planning can mediate work culture and employee involvement on employee performance, and career planning cannot mediate leadership on employee performance. The conclusion is that in improving employee performance, companies must optimize the function of work culture, leadership,and employee involvement through career planning.